Developing a rapid discharge pathway for end of life care. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Ball, Patrick; Mason, Louise
Abstract : Background: Achieving preferred place of care at end of life is a core component to national and local end of life care strategy. The specialist palliative care team at Brighton and Sussex Universities Hospitals NHS Trust introduced a pilot document and process to facilitate the discharge of patients in the final days of life. There were no formal audit process of the discharge process prior to introduction of the dedicated pathway but there were numerous complaints and feedback from patients, carers and professionals that the usual discharge process was not responsive enough for end of life care patients. Pathway: A work stream group of the Trust's end of life care development group was set up with relevant stakeholders and a pathway created to identify and clarify keys steps in successful discharge. One of the main features of our pathway is it is multi-discipline and highlights each individuals role for example, ward nurse and doctor, discharge co-ordinator and members of specialist palliative care. The pathway serves as key co-ordinating document. Pilot: In November 2011, two wards were piloted between the trusts two hospitals for 3 months. This was then extended in another ward for a further 2 months to provide more data. The Rapid Discharge Pathway was used in addition to the usual discharge documentation when a patient thought to be in the final days of life was being discharged to their home or care home with nursing. Results: Twenty-one patients were initiated on the rapid discharge pathway; of these 17 (81%) were successfully discharged to preferred place of care (11 home; 6 to Nursing home). Four patients died prior to discharge, three rapidly declined during the process and in the other difficulties arose in deciding preferred place of care. The pathway is now being rolled out across the Trust.